Analysis of risk factors of mortality in rheumatoid arthritis patients with interstitial lung disease: a nationwide, population-based cohort study in Taiwan. Issue 2 (22nd August 2022) - Ng, Kooi-Heng; Chen, Der-Yuan; Lin, Ching-Heng; Chao, Wen-Cheng; Chen, Hsin-Hua
Abstract : Objective: To examine the risk and risk factors of mortality in patients with rheumatoid arthritis (RA) with interstitial lung disease (ILD). Methods: Using the 1997–2013 Taiwanese National Health Insurance Research Database, we identified 32 289 incident patients with RA by using International Classification of Diseases, Ninth Revision codes from 2001 to 2013, and 214 patients developed ILD subsequently. We matched (1:10) RA-ILD with controls for sex, age, time of ILD diagnosis and disease duration. In addition, we conducted propensity score matching (PSM) (1:1) for selected comorbidities to choose RA-ILD patients and controls. Using the Cox proportional hazard model, we estimated the association of mortality with ILD for the two matched populations and assessed factors associated with mortality among 214 RA-ILD patients, shown as adjusted HRs (aHRs) with 95% CIs. Results: In the populations selected before and after PSM, we included 164 and 155 patients with RA-ILD and 1640 and 155 controls, respectively. ILD was associated with mortality in the population before PSM (aHR, 1.73; 95% CI 1.19 to 2.52) and in the PSM population (HR 4.38; 95% CI 2.03 to 9.43). Among 214 patients with RA-ILD, age (aHR 1.04; 95% CI 1.03 to 1.08), chronic obstructive pulmonary disease (COPD) (aHR 2.12; 95% CI 1.25 to 3.58), diabetes mellitus (DM) with end-organ damage and corticosteroid dose (prednisolone equivalent, mg/day) (aHR 1.09; 95% CI 1.07 to 1.11) were associated with mortality in RA-ILD. Conclusion: This population-based cohort study showed that ILD was associated with risk of mortality in patients with RA, and risk factors associated with mortality in patients with RA-ILD included age, COPD, DM with end-organ damage and average daily prednisolone dose.